Konsep Pendidikan Agama Islam Dalam Tinjauan Hadits (Studi Analisis Tentang Hadits-Hadits Pendidikan) - Muhamad Basyrul Muvid (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2020)
The position of the hadith in Islamic religious education becomes a basis and foundation for the concepts, framework and design of Islamic religious education, bearing in mind the hadith provides a more concrete rationale regarding the application of various activities that must be developed in the Muslim life and life framework. The concept of Islamic education in the review of educational hadiths covered includes: basic education, learning obligations, educational objectives, educational institutions, learning materials (education), learning methods, educators (teachers), students (students), women's education and evaluation learning. These ten became the basic framework in building Islamic religious education in accordance with the hadith of the Prophet.